Climate, Land, Energy and Water systems interactions – From key concepts to model implementation with OSeMOSYS. Issue 136 (October 2022) - Ramos, Eunice Pereira; Sridharan, Vignesh; Alfstad, Thomas; Niet, Taco; Shivakumar, Abhishek; Howells, Mark Idwal; Rogner, Holger; Gardumi, Francesco
Abstract: The Climate, Land, Energy and Water systems (CLEWs) approach guides the development of integrated assessments. The approach includes an analytical component that can be performed using simple accounting methods, soft-linking tools, incorporating cross-systems considerations in sectoral models, or using one modelling tool to represent CLEW systems. This paper describes how a CLEWs quantitative analysis can be performed using one single modelling tool, the Open Source Energy Modelling System (OSeMOSYS). Although OSeMOSYS was primarily developed for energy systems analysis, the tool's functionality and flexibility allow for its application to CLEWs. A step-by-step explanation of how climate, land, energy, and water systems can be represented with OSeMOSYS, complemented with the interpretation of sets, parameters, and variables in the OSeMOSYS code, is provided. A hypothetical case serves as the basis for developing a modelling exercise that exemplifies the building of a CLEWs model in OSeMOSYS. System-centred scenario analysis is performed with the integrated model example to illustrate its application. The analysis of results shows how integrated insights can be derived from the quantitative exercise in the form of conflicts, trade-offs, opportunities, and synergies. In addition to the modelling exercise, using the OSeMOSYS-CLEWs example in teaching, training and open science is explored to support knowledge transfer and advancement in the field. Highlights: Introductory nexus modelling example for initiating quantitative nexus analysis. Explanatory guidance on using an open-source tool for nexus modelling is provided. Scenarios explore the influence of sectoral and policy decisions on the nexus. Four use cases of the modelling exercise are presented.